2019
DOI: 10.21516/2072-0076-2019-12-2-49-58
|View full text |Cite
|
Sign up to set email alerts
|

The state and dynamics of the wavefront of the eye in children with different refractions engaged in regular sport activities (badminton)

Abstract: The paper is aimed at comparing the level of aberrations, structure of the wavefront, and its response to cycloplegia in children with different refractions before they started practicing badminton regularly and after a year’s duration of this practice.Material and methods. 40 children (80 eyes) with refractive errors from +6.63 to -6.75 D (average -1.28 ± 2.28 D) aged 7 to 11 years (average 9.24 ± 1.06 years) were examined before the practice, 6 months after practice start (38 children, 72 eyes) and after 1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
1
0
2
Order By: Relevance
“…One study has also been conducted which demonstrates other benefits at a physical level. This study indicated a strengthening of the lens ligaments and normalisation of the ciliary muscle tone in boys and girls with different optical refractions following a one-year badminton engagement [ 40 ], whilst fewer postural asymmetries were found in adolescent boys playing badminton relative to adolescents not playing any sport [ 36 ]. Further outcomes included higher high-density lipoprotein (HDL) cholesterol levels, associated with a reduced likelihood of coronary heart disease, in adults and elderly men and women [ 39 ]; improved body shape in adolescent females due to the effect of badminton on development in the specific limb dimensions engaged during play [ 26 ] and better functional physical fitness and self-perceived functional health in the elderly, regardless of sex, alongside retarded biological degradation [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study has also been conducted which demonstrates other benefits at a physical level. This study indicated a strengthening of the lens ligaments and normalisation of the ciliary muscle tone in boys and girls with different optical refractions following a one-year badminton engagement [ 40 ], whilst fewer postural asymmetries were found in adolescent boys playing badminton relative to adolescents not playing any sport [ 36 ]. Further outcomes included higher high-density lipoprotein (HDL) cholesterol levels, associated with a reduced likelihood of coronary heart disease, in adults and elderly men and women [ 39 ]; improved body shape in adolescent females due to the effect of badminton on development in the specific limb dimensions engaged during play [ 26 ] and better functional physical fitness and self-perceived functional health in the elderly, regardless of sex, alongside retarded biological degradation [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…4). Ранее нами были опубликованы результаты исследований волнового фронта у детей с различной рефракцией без ПИНА и псевдомиопии [17].…”
Section: результатыunclassified
“…Нам представляется, что эти особенности можно связать с состоянием связочного аппарата хрусталика и цилиарной мышцы. Повышенный уровень аберраций, связанных с наклоном хрусталика, его смещением, децентрацией оптических элементов глаза, может свидетельствовать о слабом натяжении связок (возможно, связанном с избыточным тонусом цилиарной мышцы) [43].…”
unclassified